WOS: an Internet computing environment - Kropf, Peter; Unger, Herwig; Babin, Gilbert (: IEEE, 2000)
Given the current development of the Internet, the Web, mobile communications and services, we are clearly head- ing towards an era of widely integrated ubiquitous services sharing some kind of global operating system. This arti- cle describes the idea, the objectives and the current state of the development of the WOS-project. The Web Operat- ing System (WOS") consists of a series of versioned servers where each one can offer different services, themselves ver- sioned. Each node can act as a server or a client. A com- mon protocol, itself versioned, is used for communication among WOSNodes. Requests for services can be passed on to other servers as appropriate. The WOS is defined by the combined actions of different nodes.
, 2000